2012
DOI: 10.3758/s13414-012-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Coarse guidance by numerosity in visual search

Abstract: In five experiments, we examined whether the number of items can guide visual focal attention. Observers searched for the target area with the largest (or smallest) number of dots (squares in Experiment 4 and “checkerboards” in Experiment 5) among distractor areas with a smaller (or larger) number of dots. Results of Experiments 1 and 2 show that search efficiency is determined by target to distractor dot ratios. In searches where target items contained more dots than did distractor items, ratios over 1.5:1 yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Based on previous research on selective attention using visual search tasks, we expected the TBF/TBR ratio to modulate the SDF effect. Reijnen et al (2013) found that search efficiency is determined by the target-to-distractor ratio rather than by the absolute difference between the number of distractor and target stimuli. Of relevance for our study, they found an asymmetry effect whereby searching for a smaller number of items among a large set was harder than searching for a larger number among a smaller set of items.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Based on previous research on selective attention using visual search tasks, we expected the TBF/TBR ratio to modulate the SDF effect. Reijnen et al (2013) found that search efficiency is determined by the target-to-distractor ratio rather than by the absolute difference between the number of distractor and target stimuli. Of relevance for our study, they found an asymmetry effect whereby searching for a smaller number of items among a large set was harder than searching for a larger number among a smaller set of items.…”
Section: Methodsmentioning
confidence: 94%
“…Based on previous findings in the realm of visual selective attention (Reijnen et al, 2013), we assumed that correctly performing the SDF task (that is, selecting the forget items and forgetting them) might be harder with low proportion of TBF items. The results of Experiment 3 support this assumption and indicate that the TBF/TBR items ratio modulates the ability to intentionally forget in a selective way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be argued that, in the numerosity comparison task performed in the above experiments, the comparison judgment could be confounded by other perceptual attributes of the displays, such as density or area, and other local features rather than being based on the actual representation of dot numerosity (17)(18)(19)(20)(21)(22)(23)(24). We, therefore, used, instead of the comparison task, a subjective estimation task, which required observers to report the number of dots directly (19).…”
Section: Significancementioning
confidence: 99%